2020
DOI: 10.21203/rs.3.rs-33391/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 Therapeutics Outcome: Systematic Review and Data Analysis

Abstract: Background: Several medications already placed in the world therapeutic guidelines for coronavirus disease 2019 (COVID-19) were given to affected patients and produced positive and negative outcomes.Aims of the study: This review evaluated therapeutic outcomes (recovery and mortality) used for COVID-19 patient management in clinical settings since the emergence of SARS-CoV-2 the causative agent of (COVID-19).Method: The PRISMA-P and PRISMA statements were used to facilitate the development and reporting of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…In a recent systematic review (preprint version) that included 69 studies which included therapeutics for COVID-19, lopinavir/ritonavir was found to be the third therapeutic associated with positive outcomes (54.9%) with less negative outcomes (12.3%) compared to systemic corticosteroids (21.3%), remdesivir (16.9%), moxioxacin (13.4%) and oseltamivir (12.5%) [36]; however, further controlled studies are needed to draw a valid conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent systematic review (preprint version) that included 69 studies which included therapeutics for COVID-19, lopinavir/ritonavir was found to be the third therapeutic associated with positive outcomes (54.9%) with less negative outcomes (12.3%) compared to systemic corticosteroids (21.3%), remdesivir (16.9%), moxioxacin (13.4%) and oseltamivir (12.5%) [36]; however, further controlled studies are needed to draw a valid conclusion.…”
Section: Discussionmentioning
confidence: 99%